2013
DOI: 10.1152/japplphysiol.00978.2012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of breaking up prolonged sitting on skeletal muscle gene expression

Abstract: Breaking up prolonged sitting has been beneficially associated with cardiometabolic risk markers in both observational and intervention studies. We aimed to define the acute transcriptional events induced in skeletal muscle by breaks in sedentary time. Overweight/obese adults participated in a randomized three-period, three-treatment crossover trial in an acute setting. The three 5-h interventions were performed in the postprandial state after a standardized test drink and included seated position with no acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
102
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 135 publications
(107 citation statements)
references
References 30 publications
2
102
0
3
Order By: Relevance
“…34 Other research has demonstrated that prolonged sitting is associated with the expression of various genes linked to inflammatory responses. 35 Adipose tissue inflammation might also explain links between sedentary behaviour and inflammation. 36 Indeed, reductions in central adiposity largely explain the changes in CRP observed after aerobic exercise training interventions.…”
Section: Discussionmentioning
confidence: 99%
“…34 Other research has demonstrated that prolonged sitting is associated with the expression of various genes linked to inflammatory responses. 35 Adipose tissue inflammation might also explain links between sedentary behaviour and inflammation. 36 Indeed, reductions in central adiposity largely explain the changes in CRP observed after aerobic exercise training interventions.…”
Section: Discussionmentioning
confidence: 99%
“…As more experimental studies continue to emerge, it is becoming increasingly clear that there are likely to be multiple complex mechanisms and interacting pathways involved with cardiometabolic health. For instance, recent studies suggest that responses to sedentary behaviour may also be diet/energy intake related [39], or even linked to fibrinolytic factors [60] and skeletal muscle gene expression [61,62].…”
Section: Better Understand the Underlying Mechanistic Effects Of Sedementioning
confidence: 99%
“…Breaking up SB with LIPA or MIPA increases the expression of the gene that encodes for dynein light chain 1 (DNLL1). DNLL1 plays a role in the transcription of GLUT-4 in middle aged to older adults (Latouche et al 2013) and is thought to be part of a mechanism for GLUT-4-induced reduction in plasma glucose during SB breaks. Insulin concentration may increase to compensate for the reduction in glucose uptake via the GLUT-4 pathway but consequently cause a decline in skeletal muscle insulin sensitivity.…”
Section: Sedentary Behaviour and Physical Activity: Impact On Glucosementioning
confidence: 99%